1998
DOI: 10.1128/iai.66.12.5613-5619.1998
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Immunologic Analyses of PlpE, a Lipoprotein Important in Complement-Mediated Killing ofPasteurella haemolyticaSerotype 1

Abstract: Pasteurella haemolytica serotype 1 is the bacterium most commonly associated with bovine shipping fever. The presence of antibodies against P. haemolytica outer membrane proteins (OMPs) correlates statistically with resistance to experimental P. haemolytica challenge in cattle. Until now, specific P. haemolytica OMPs which elicit antibodies that function in host defense mechanisms have not been identified. In this study, we have cloned and sequenced the gene encoding one such protein, PlpE. Analysis of the ded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 40 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…A surface-exposed 45-kDa OMP, designated PlpE, was sequenced and cloned by Pandher et al (1999) . Mosier et al (1989) reported this protein to be immunogenic in cattle and Pandher et al (1998) found that antibodies to PlpE were associated with complement-mediated killing of M. haemolytica . A recombinant PlpE was highly immunogenic when injected subcutaneously in vaccination studies (Confer et al , 2003).…”
Section: Bacterial Virulence Factorsmentioning
confidence: 99%
“…A surface-exposed 45-kDa OMP, designated PlpE, was sequenced and cloned by Pandher et al (1999) . Mosier et al (1989) reported this protein to be immunogenic in cattle and Pandher et al (1998) found that antibodies to PlpE were associated with complement-mediated killing of M. haemolytica . A recombinant PlpE was highly immunogenic when injected subcutaneously in vaccination studies (Confer et al , 2003).…”
Section: Bacterial Virulence Factorsmentioning
confidence: 99%
“…Outer membrane proteins and lipoproteins of M. haemolytica may be involved in serum sensitivity (111,112) and they are believed to be important protective antigens. Antibodies directed against some of these antigens are capable of inducing phagocytosis and complement-mediated killing (112). As a result, these surface-exposed proteins are of interest as potential vaccine candidates.…”
Section: Outer Membrane Proteinsmentioning
confidence: 99%
“…Though the M. haemolytica pomA gene has been cloned, attempts to inactivate it have been unsuccessful (G. Murphy, personal communication), suggesting that PomA may be involved in transport of nutrients or that it may be critical to the integrity of the outer membrane. M. haemolytica also produces at least five distinct lipoproteins with apparent molecular weights that range from 19 to 45 kD (112,(114)(115)(116). A mutant lacking three of these lipoproteins (PlpA, PlpB and PlpD) was created by allelic exchange using the ROB-1 beta-lactamase gene from M. haemolytica (117).…”
Section: Outer Membrane Proteinsmentioning
confidence: 99%
“…Therefore, our work has focused on identifying and characterizing P. haemolytica OMPs with surface domains that are targets of antibodies present in sera from immune cattle (30). We found that the 45-kDa lipoprotein (PlpE) elicits bovine antibodies that effect complement-medi-ated killing of P. haemolytica (28). Our previous studies with PomA revealed that it is recognized by antibodies from cattle immune to P. haemolytica challenge and that it possesses surface-exposed regions (21).…”
mentioning
confidence: 99%
“…The sera were from cattle that were resistant to experimental P. haemolytica challenge after natural exposure to the bacterium or after vaccination with live P. haemolytica or with P. haemolytica OMPs (30). Sera were absorbed with intact P. haemolytica cells as previously described (28). Absorbed and unabsorbed sera, diluted 1:100 in Tris-saline-nonfat dry milk (TSM) (10mM Tris [pH 7.4], 0.9% [wt/vol] NaCl, 1% nonfat dry milk), were used to probe Western immunoblots of purified rPomA and P. haemolytica whole-cell lysates (Fig.…”
mentioning
confidence: 99%